English Teachers' Strategies in Teaching Reading Comprehension and the Challenges Encountered - Rana Afifatuz Zhofiroh; Nuraeningsih Nuraeningsih; Farid Noor Romadlon (JALL (Journal of Applied Linguistics and Literacy), 2026)
This research aims to describe the strategies used by English teachers in teaching reading comprehension at SMAN 1 Jekulo and to identify the challenges faced during their implementation. The background of this study is the fact that many students still have difficulties in understanding English texts due to limited vocabulary, lack of mastery of reading strategies, and low learning motivation. This study applied a descriptive qualitative method. The data obtained through classroom observations as well as interviews with four English educators. The results show the teachers used a number of tactics, like scaffolding, think-aloud, reciprocal teaching, SQ3R, and QAR. The usage of these tactics was adapted to the students' competence stage, course objectives, and genre of literature. In mixed-ability classes, teachers also made certain adaptations, such as providing extra assistance to struggling students and assigning more difficult assignments to students who were more competent. Several problems remain, such as limits vocabulary, student ability gaps, a lack of enthusiasm in reading, and limited time in the classroom. However, the implementation of these strategies improved students' reading comprehension and made the class more interesting. The findings of this study are expected to provide teachers with suggestions for selecting and developing reading techniques, and they will also serve as an example for future researchers researching into ways for teaching reading comprehension in different situations.